Analysis of floating refuse along the Gombak River - Yong, Eu Fan; Tan, Ka Kheng (Universiti Pertanian Malaysia, 1988)
Data were collected on the types and weights of floating refuse along the Gombak River off Jalan Sentul in Kuala Lumpur over a period of 6 months. Based on the samples taken, the refuse was divided into different categories and their proportions by weight and average bulk density were estimated. It was found that the largest component by weight (42%) of the refuse consisted of cans, containers and other products made from metal. The average bulk density of the wet refuse was about 100 kg/m 3 . Suggestions are also made with regards to the best methods to collect the floating refuse and to clean up the rivers in the Kuala Lumpur City area based on the characteristics of the waste and an assessment of the various methods being currently tested.